2021
DOI: 10.12911/22998993/139000
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Soil Macrofauna in Jelutong (<i>Dyera lowii</i> Hook.F) based Agroforestry System on Peatlands

Abstract: Soil macrofauna can be an indicator of changes to the ecosystem. This study aimed to investigate the biodiversity of soil macrofauna in jelutong-based agroforestry on peatlands. Line transect sampling was used, eight transects and 32 plots were established. The sample was collected using the hand sorting technique. Species diversity and species evenness were determined using Shannon-Wiener index, while species richness with Margalef index. This study found 2179 individuals of soil macrofauna that belong to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Lichtenstein et al [16] explained that the presence of predators and the abundance of predators are influenced by the presence of prey and the behavior of the prey. The results of a study by Johari et al [17] which explored the diversity of ant species in peatlands, also did not find M. castanea ants in oil palm plantations on the peatlands they explored, as well as the results of research by Yanarita et al [18] which only found obtained 2 types of ant species, namely Solenopsis invicta and Monomorium minimum in the peatland of the Jelutong forest, Central Kalimantan. Peatland often has special characteristics such as high acidity and low water content.…”
Section: Resultsmentioning
confidence: 90%
“…Lichtenstein et al [16] explained that the presence of predators and the abundance of predators are influenced by the presence of prey and the behavior of the prey. The results of a study by Johari et al [17] which explored the diversity of ant species in peatlands, also did not find M. castanea ants in oil palm plantations on the peatlands they explored, as well as the results of research by Yanarita et al [18] which only found obtained 2 types of ant species, namely Solenopsis invicta and Monomorium minimum in the peatland of the Jelutong forest, Central Kalimantan. Peatland often has special characteristics such as high acidity and low water content.…”
Section: Resultsmentioning
confidence: 90%